Investigation of Scientific Reasoning Skills Survey Research on Static Fluid Topics - Ari, Patricius; Parno, Parno; Khusaini, Khusaini; Bunyamin, Muhammad Abd Hadi (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2024)
The aim of this study is to evaluate the level of students' scientific reasoning skills in the subject of static fluids. This research was conducted through a descriptive quantitative survey. The study involved 110 high school students from Grade 12 in Malang, Indonesia, during the 2023/2024 academic year. Six scientific reasoning skill test instruments were used to collect data. The data collection was carried out using six test instruments, covering Control of Variables, Conservation Reasoning, Probabilistic Reasoning, Correlational Reasoning, Hypothetical-Deductive Reasoning, and Proportional Reasoning, with a Cronbach's alpha of 0.744, indicating high reliability. The data were analyzed using descriptive statistical tests, followed by classification of skill levels based on static fluid subtopics and scientific reasoning indicators. According to the survey results, 33% of students demonstrated low-level scientific reasoning skills. Based on the static fluid subtopics, the highest to lowest scores were found in Archimedes' Principle (35%), hydrostatic pressure (34%), and Pascal's Law (31%), all within the low category. In terms of scientific reasoning sub-indicators, the highest to lowest scores were observed in Hypothetical-Deductive Reasoning (42%) and Probabilistic Reasoning (41%), categorized as moderate, while lower scores were found in Correlational Reasoning (39%), Conservation Reasoning (29%), Control of Variables (26%), and Proportional Reasoning (24%), all within the low category. The results suggest that students struggle with analyzing factors affecting sinking, floating, and buoyancy; identifying variables influencing hydrostatic pressure; and performing mathematical calculations related to force and cross-sectional area comparisons. These findings indicate that instruction needs to be strengthened to help students improve their scientific reasoning, particularly in the indicators of Conservation Reasoning, Control of Variables, and Proportional Reasoning, which remain low. To maximize the effectiveness of this research, educators should employ active learning models such as the 7E Learning Cycle Model integrated with the STEAM approach, which can directly engage students.